2024
DOI: 10.1039/d4ee00798k
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation mechanism of lithium salt by BaTiO3 with spontaneous polarization

Shaoke Guo,
Shendong Tan,
Jiabin Ma
et al.

Abstract: In composite solid-state electrolytes, the functional fillers with ferroelectric properties have demonstrated their ability to prompt the dissociation of lithium salt (LiFSI), thereby significantly enhancing ionic conductivity. However, the underlying...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
0
0
Order By: Relevance
“…Through the analysis of Fourier transform infrared (FT-IR) spectra, they concluded that the surface groups of BaTiO3 particles interact with PEO chains and lead to the weakening of the complexation between Li ions and O atoms. Recently, Guo and coworkers [19] studied the dissociation mechanism of lithium bis(fluorosulfonyl)imide (LiFSI) induced by BaTiO3 ferroelectric filler in BaTiO3-PVDF electrolyte (PVDF: polyvinylidene fluoride) and found that the {100} plane of tetragonal-BaTiO3 exhibits a significant ability to dissociate lithium salts and accumulate anions, which is due to the surface absorption of FSI − formed by the bind-ing between O in FSI − and Ti in tetragonal BaTiO3. The introduction of oxygen vacancies in tetragonal BaTiO3 enhances the spontaneous polarization of the fillers, further increasing the dissociation degree of lithium salts and giving rise to an ionic conductivity of 8.4 × 10 −4 S•cm −1 at 25 ∘ C.…”
mentioning
confidence: 99%
“…Through the analysis of Fourier transform infrared (FT-IR) spectra, they concluded that the surface groups of BaTiO3 particles interact with PEO chains and lead to the weakening of the complexation between Li ions and O atoms. Recently, Guo and coworkers [19] studied the dissociation mechanism of lithium bis(fluorosulfonyl)imide (LiFSI) induced by BaTiO3 ferroelectric filler in BaTiO3-PVDF electrolyte (PVDF: polyvinylidene fluoride) and found that the {100} plane of tetragonal-BaTiO3 exhibits a significant ability to dissociate lithium salts and accumulate anions, which is due to the surface absorption of FSI − formed by the bind-ing between O in FSI − and Ti in tetragonal BaTiO3. The introduction of oxygen vacancies in tetragonal BaTiO3 enhances the spontaneous polarization of the fillers, further increasing the dissociation degree of lithium salts and giving rise to an ionic conductivity of 8.4 × 10 −4 S•cm −1 at 25 ∘ C.…”
mentioning
confidence: 99%